Evaluation of the archives and records management practices of the Malate Catholic Church restoration project - Hontiveros, Maria Angelica B. (School of Library and Information Studies, University of the Philippines, Diliman, 2019)
Heritage conservation is an activity that preserves the built heritage or architectural heritage of a specific culture or country. As an activity that converge architecture, history, and other related fields, a conservation or restoration project produces huge volume of records throughout the span of project. As a results, various guidelines and recommendations were prescribed to manage these records and documentation in order to make the most of these records. In an effort to identify and evaluate the records management and archival practices of a heritage conservation project, the records of the Malate Catholic Restoration Project were evaluated in comparison to Jenkinson's appraisal theory and other prevailing standards in records management using the ISO 15489 as methodology. The results of the study indicate that the type of records produced for the project is at par with the standards. However, the restoration project needs an efficient records management plan and manual for its users. The recommendation can be applied in order to improve on existing practices and future projects.